Differential roles of IL-1 and TNF-α on graft-versus-host disease and graft versus leukemia - Hill, Geoffrey R. (American Society for Clinical Investigation, 1999)
We demonstrate an increase in graft-versus-host disease (GVHD) after experimental bone marrow transplant (BMT) when cyclophosphamide (Cy) is added to an otherwise well-tolerated dose (900 cGy) of total body irradiation (TBI). Donor T cell expansion on day +13 was increased after conditioning with Cy/TBI compared with Cy or TBI alone, although cytotoxic T lymphocyte (CTL) function was not altered. Histological analysis of the gastrointestinal tract demonstrated synergistic damage by Cy/TBI and allogeneic donor cells, which permitted increased translocation of LPS into the systemic circulation. TNF-α and IL-1 production in response to LPS was increased in BMT recipients after Cy/TBI conditioning. Neutralization of IL-1 significantly reduced serum LPS levels and GVHD mortality, but it did not affect donor CTL activity. By contrast, neutralization of TNF-α did not prevent GVHD mortality but did impair CTL activity after BMT. When P815 leukemia cells were added to the bone marrow inoculum, allogeneic BMT recipients given the TNF-α inhibitor relapsed at a significantly faster rate than those given the IL-1 inhibitor. To confirm that the role of TNF-α in graft versus leukemia (GVL) was due to effects on donor T cells, cohorts of animals were transplanted with T cells from either wild-type mice or p55 TNF-α receptor–deficient mice. Recipients of TNF-α p55 receptor–deficient T cells demonstrated a significant impairment in donor CTL activity after BMT and an increased rate of leukemic relapse compared with recipients of wild-type T cells. These data highlight the importance of conditioning in GVHD pathophysiology, and demonstrate that TNF-α is critical to GVL mediated by donor T cells, whereas IL-1 is not. J. Clin. Invest. 104:459-467 (1999).